2016
DOI: 10.1063/1.4955142
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the spectral emittance of α-SiC open-cell foams up to 1300 K with their macro porosity

Abstract: A simple and robust analytical model is used to finely predict the spectral emittance under air up to 1300 K of α-SiC open-cell foams constituted of optically thick struts. The model integrates both the chemical composition and the macro-porosity and is valid only if foams have volumes higher than their Representative Elementary Volumes required for determining their emittance. Infrared emission spectroscopy carried out on a doped silicon carbide single crystal associated to homemade numerical tools based on 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…In 2016, Rousseau et al proposed a numerical analysis model for predicting the spectral emissivity of porous SiC-based foams in high-temperature environments . Studies have shown that the smaller the internal pores of the SiC-based foam, the higher the porosity, which leads to a more tortuous skeleton structure and better thermal insulation performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Rousseau et al proposed a numerical analysis model for predicting the spectral emissivity of porous SiC-based foams in high-temperature environments . Studies have shown that the smaller the internal pores of the SiC-based foam, the higher the porosity, which leads to a more tortuous skeleton structure and better thermal insulation performance.…”
Section: Resultsmentioning
confidence: 99%
“…In 2016, Rousseau et al proposed a numerical analysis model for predicting the spectral emissivity of porous SiCbased foams in high-temperature environments. 51 Studies have shown that the smaller the internal pores of the SiC-based foam, the higher the porosity, which leads to a more tortuous skeleton structure and better thermal insulation performance. In order to explain the excellent thermal insulation performance of the SiC nw @SiC foam more intuitively, the schematic diagram of the heat transfer mechanism is shown in Figure 8b.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting mode, known as for Longitudinal Optical phonon Plasmon Coupled, will be treated in the next part as a phonon-like type particle. Thirdly, the simulations will be IHTC16-24216 3 carried out only at = 300 K since higher temperatures do not modify ̃, , as it can be shown for = 10 19 cm -3 by infrared emittance spectroscopy [17]. Once these basis are settled, the MD technique consists in applying the Newton's second law for computing all positions, , and velocities, ̇, for each atoms as a function of the time .…”
Section: Molecular Dynamics For the Computation Of The Complex Dielecmentioning
confidence: 99%
“…1b. The thin and thick green curves give the spectral dependence at = 300 K of the complex refractive index of a doped SiC single crystal used to compute the radiative properties of opencell foams with growing porosities and nominal pore diameters [17]. The evolutions of the index of refraction , and absorption , match here completely those obtained by our molecular dynamic approach, knowing that for the two samples are rather identical: around 10 19 cm -3 in [17] and 1.2 10 19 cm -3 in this work (red curves).…”
Section: Microscopic Evolution Of the Complex Dielectric Functions Wimentioning
confidence: 99%